2020
DOI: 10.1515/remav-2020-0023
|View full text |Cite
|
Sign up to set email alerts
|

Model Hybrid for Sales Forecast for the Housing Market of São Paulo

Abstract: This research proposes a combined model of time series for forecasting housing sales in the city of São Paulo. We used data referring to the time series of sales of residential units provided by SECOVI-SP. The Exponential Softening, Box-Jenkins and Artificial Neural Networks models are individually modelled, later these are combined through five forecast combination techniques.The techniques used are Arithmetic Mean, Geometric Mean, Harmonic Mean, Linear Regression and Principal Component Analysis. The measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…A broader approach was taken by Moro et al (2020), who combined five forecast combination techniques and proposed a combined model to forecast property sales using time series data and by modelling using the Box-Jenkins, exponential softening, and ANN techniques. Zlateva et al (2011) assessed the investment risks in real estate for sustainable regional development and proposed a fuzzy logic model as a hierarchical system with various variables.…”
Section: Management Of Technology In Real Estatementioning
confidence: 99%
“…A broader approach was taken by Moro et al (2020), who combined five forecast combination techniques and proposed a combined model to forecast property sales using time series data and by modelling using the Box-Jenkins, exponential softening, and ANN techniques. Zlateva et al (2011) assessed the investment risks in real estate for sustainable regional development and proposed a fuzzy logic model as a hierarchical system with various variables.…”
Section: Management Of Technology In Real Estatementioning
confidence: 99%
“…According to Miller et al (2011), housing prices play an important role in GDP growth. Furthermore, civil construction is one of the leading sectors of the economy (Moro et al, 2020), and real estate is a medium and long-term investment industry, which has a long return period (Huang et al, 2011). Last but not least, the real estate market is mainly determined by the financial market (Anghel & Hristea, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Through experiments, they found that the addition of Google Trends data could reduce the mean absolute percentage error (MAPE) by 2.2% to 7.7%. To predict housing sales in São Paulo, Moro et al [6] modeled the index softening, Box-Jenkins, and artificial neural network models and compared their effects using different combinations. Ma et al [7] applied the genetic algorithm-back-propagation neural network (GA-BPNN) algorithm to the sales forecast of electric vehicles.…”
Section: Introductionmentioning
confidence: 99%